Production, isolation and characterization of bioactive peptides with antihypertensive properties from rapeseed and potato protein - Mäkinen, Sari (fi=Turun yliopisto|en=University of Turku|, 2014)
Consumers’ increasing awareness of healthiness and sustainability of food presents a great challenge to food industry to develop healthier, biologically active and sustainable food products. Bioactive peptides derived from food proteins are known to possess various biological activities. Among the activities, the most widely studied are antioxidant activities and angiotensin I converting enzyme (ACE) inhibitory activity related to blood pressure regulation and antihypertensive effects. Meanwhile, vast amounts of byproducts with high protein content are produced in food industry, for example potato and rapeseed industries. The utilization of these by-products could be enhanced by using them as a raw material for bioactive peptides. The objective of the present study was to investigate the production of bioactive peptides with ACE inhibitory and antioxidant properties from rapeseed and potato proteins. Enzymatic hydrolysis and fermentation were utilized for peptide production, ultrafiltration and solid-phase extraction were used to concentrate the active peptides, the peptides were fractionated with liquid chromatographic processes, and the peptides with the highest ACE inhibitory capacities were putified and analyzed with Maldi-Tof/Tof to identify the active peptide sequences. The bioavailability of the ACE inhibitory peptides was elucidated with an in vitro digestion model and the antihypertensive effects in vivo of rapeseed peptide concentrates were investigated with a preventive premise in 2K1C rats. The results showed that rapeseed and potato proteins are rich sources of ACE inhibitory and antioxidant peptides. Enzymatic hydrolysis released the peptides effectively whereas fermentation produced lower activities.The native enzymes of potato were also able to release ACE inhibitory peptides from potato proteins without the addition of exogenous enzymes. The rapeseed peptide concentrate was capable of preventing the development of hypertension in vivo in 2K1C rats, but the quality of rapeseed meal used as raw material was found to affect considerably the antihypertensive effects and the composition of the peptide fraction.